Pengaruh Metode Pembayaran COD Terhadap Keputusan Pembelian Mahasiswa Pada Aplikasi Shopee - Saidah Nur; Andy Hakim; Sari Fitri (Studia Economica : Jurnal Ekonomi Islam, 2025)
The aim of the research is to analyze the influence of the COD payment method variable on students purchasing decision variables on the Shopee platform. This research used a quantitative approach involving 75 respondents. Primary data was collected through questionnaires and analyzed statistically using SPSS 25 software. The results of this study show that the Cash On Delivery (COD) payment method influences the purchasing decisions of STAIN Mandailing Natal sharia business management students with a value of tcount = 8.721, ttable = 1.293 and sig = 0.000 at a significant level of 0.1. So, 0.000 < 0.1 and 8.721 > 1.293 means Ha is accepted and H0 is rejected. The Cash On Delivery (COD) payment method has a variable influence of 51% on purchase decisions, with a coefficient of determination (R2) of 0.510. Other factors not included in this study influence the remaining 49%. Based on the analysis findings, the decision of STAIN Mandailing Natal sharia business management students to buy at the Shopee Marketplace was influenced by the Cash On Delivery (COD) payment option